Bone marrow stroma‐mediated resistance to FLT3 inhibitors in FLT3‐ITD AML is mediated by persistent activation of extracellular regulated kinase. (10th October 2013) - Yang, Xiaochuan; Sexauer, Amy; Levis, Mark
Summary A consistent pattern of response has been observed when FMS‐like tyrosine kinase 3 (FLT3) tyrosine kinase inhibitors (TKIs) have been used as monotherapy to treat patients with relapsed or refractory FLT3‐ internal tandem duplication (ITD) acute myeloid leukaemia (AML). Circulating blasts are cleared from the peripheral blood, while bone marrow blasts are either unaffected or are cleared from the marrow at a much slower rate. We used an in vitro model of FLT3‐ITD AML blasts co‐cultured with normal human bone marrow stromal cells to investigate the basis for this dichotomous response pattern to FLT3 inhibitors. We have found that in blasts on stroma, potent FLT3 inhibition predominantly results in cell cycle arrest rather than apoptosis. The anti‐apoptotic effect is mediated through a combination of direct cell‐cell contact and soluble factors. The addition of exogenous FLT3 ligand (FL) augments the protection, primarily by shifting the 50% inhibitory concentration for FLT3 inhibition upwards. Cytokine‐activated extracellular regulated kinase (ERK), rather than STAT5, appears to be the most important downstream signalling protein mediating the protective effect, and inhibition of MEK significantly abrogates stromal‐mediated resistance. These findings explain the phenomenon of peripheral blood versus bone marrow blast responses and suggest that the combination of potent FLT3 inhibition and MEK inhibition is a promising strategy for the treatment of FLT3‐ITD AML.